Concentración de nitrogeno y fósforo en el agua de lluvia de Corrientes (Argentina) - Pedrozo, Fernando L.; Bonetto, Carlos A. (Ecosur, 2023)
Inorganic nitrogen, phosphorus, pH and conductivity in rainwater were measured at Corrientes (27°27’S, 58°47’W) during 1984-1985. Mean water pH was 5.97 (4.60 - 7.15) and mean conductivity was 11.5 uS/cm (2.7 - 21 uS/cm) showing good water quality. Concentration showed positive correlation with the length of time between successive rains and were inversely correlated with precipitation volume. Both inorganic nitrogen concentrations and fallout, were low (mean conc.: 315 µg Ninorg/1 mean fallout: 190 µg Ninorg/m2 yr) when compared with the reported figures in unpolluted locations. Total phosphorus concentration (36 µg TP/1) and fallout (16.5 µg TP/m2 yr) were relatively high probably because of dust contribution. Fallout rates resulted an order of magnitude lower than those of very polluted areas.lt was shown that nutrient fallout is important in determining trophic status of shallow lakes and ponds profuselly distributed in Corrientes province.